Comparative Study of Levels of Academic Self Esteem and Academic Achievement in Mathematics among Pupils of Two and Single Parent Families - Unamba Unamba; Okwara Kalu; Ibe Georgeline (Malikussaleh Journal of Mathematics Learning (MJML), 2020)
The study aimed at comparing levels of academic self-esteem and academic achievement in mathematics among students of two and single parent families. Based on the purposes of the study two research questions and two null hypotheses were formulated and tested at 0.05 level of significance. The design of the study was comparative survey research design. The population of the study comprised all 1,267 SS2 students in Owerri Municipal Council Area of Imo State. The instruments used for data collection were Academic Self Esteem Questionnaire (ASEQ) and Mathematics Achievement Test (MAT) to obtain relevant data. The validity of the instruments was done by experts in Measurement and Evaluation and one expert each from Educational psychology and Mathematics Education. The reliability of the instruments was 0.72 and 0.85, determined using Pearson Product Moment Correlational (PPMC) statistics were used. Data collected were analyzed using t-test at 0.05 level of significance. There is a statistically significant difference in levels of academic self-esteem and academic achievement in mathematics among students from single parent families and those from two parent families.